Chapter 13 The value of the imagined biological in policy and society Somaticizing and economizing British subject(ivitie)s - Pickersgill, Martyn (Taylor & Francis, 2018)
Attending the World Economic Forum this past week, I was struck by two trends. The first was that brain research has emerged as a hot topic. Not only was brain science or brain health a new theme at the meeting, research on the brain emerged in discussions about next generation computing, global cooperation, and even models of economic development as well as being linked to mental health or mindfulness. In a meeting frequented largely by economists and business leaders, I was surprised by the number of non-scientists who have become enchanted by brain science. Clearly this is the era of the brain, with mental health now part of a much broader discussion.